LEGAL PROTECTION FOR WOMEN AND CHILD VICTIMS OF SEXUAL VIOLENCE AT THE WOMEN AND CHILDREN PROTECTION UNIT OF THE TEBING TINGGI MUNICIPAL POLICE - Siahaan, Hayati; Siregar, Taufik; Rafiqi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the form of legal protection for women and children victims of sexual violence in the Women and Children Protection Unit (PPA) of the Tebing Tinggi City Police, as well as assess the effectiveness of the implementation of laws and regulations in the process of handling them. This research uses a normative juridical method with a legislative approach and a case approach. Data were obtained through literature studies on primary, secondary, and tertiary legal materials, and were analyzed qualitatively through legal interpretation. The results of the study show that normatively legal protection mechanisms have been regulated in various regulations, including the Child Protection Law and provisions related to sexual violence. At the implementation level, there are still obstacles in the aspects of victim assistance, the speed of case handling, and the consistency of the application of criminal sanctions. This study emphasizes the need to strengthen coordination between law enforcement and optimize victim psychological protection to realize substantive justice.